Níveis de apropriação das TDIC pelos professores - Lima, Joyce Aparecida (2019)
This dissertation is part of the New Technologies in Education research line of the Postgraduate Program in Education: curriculum of the Pontifical Catholic University of São Paulo. The objective of this study was to analyze and identify the levels of appropriation of TDIC by the teachers. The author used two research methods: Application of a questionnaire, duly approved by the Research Ethics Committee, at a private higher education institution in São Paulo. The questionnaire was intended for postgraduate students in education who act as educators; and Analysis of texts and documents produced by bodies and authors treated as reference in TDIC by the author, such as Sandholtz, Ringstaff and Dwyer (1997), Moersh (1995), UNESCO (2008), European Framework for the Digital Competence of Educators DIGCOMPEDU) (2017), for Technology in Education (ISTE) (2017), CIEB (2017) and Pasinato, Vosgerau (2011). Through the analysis of the questionnaires it was observed that, among others, the participants act as educators in public and / or private primary schools. They also affirmed to use TDIC in their routine and in their pedagogical practices. Based on the models of Pasinato & Vosgerau (2011) and the CIEB (2017) matrix, the levels of appropriation of participants' TDIC were evaluated. At the end, it can be concluded that, through the methodological approach adopted, it was possible to analyze and identify the levels of appropriation of TDIC of the participating teachers. In addition, it was verified that the participants presented a high level of knowledge of TDIC